Elizabeth Robins Pennell : critical essays - Buchanan, Dave, 1967-; Jones, Kimberly Morse (Edinburgh critical studies in Victorian culture., 2021)
An edited collection of interdisciplinary essays on the work of Elizabeth Robins Pennell, American-born, London-based journalist, author, and aesthete who published (or co-published) over twenty books and a thousand periodical articles between the early 1880s and 1930.